2017
DOI: 10.3847/1538-4357/aa76dd
|View full text |Cite
|
Sign up to set email alerts
|

The MUSCLES Treasury Survey. IV. Scaling Relations for Ultraviolet, Ca ii K, and Energetic Particle Fluxes from M Dwarfs

Abstract: Characterizing the UV spectral energy distribution (SED) of an exoplanet host star is critically important for assessing its planet's potential habitability, particularly for M dwarfs, as they are prime targets for current and nearterm exoplanet characterization efforts and atmospheric models predict that their UV radiation can produce photochemistry on habitable zone planets different from that on Earth. To derive ground-based proxies for UV emission for use when Hubble Space Telescope (HST) observations are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 161 publications
(289 reference statements)
8
114
1
Order By: Relevance
“…The Lyman-α and Si iii lines do not appear redshifted during the flare, as is sometimes the case for chromospheric and transition region lines (e.g. Pillitteri et al 2015, Youngblood et al 2017. We see no sign of the flare in the N v doublet, even though an increase on the order of that in the Si iii line would have been detected.…”
Section: Visit B -September 7/8 2011supporting
confidence: 67%
“…The Lyman-α and Si iii lines do not appear redshifted during the flare, as is sometimes the case for chromospheric and transition region lines (e.g. Pillitteri et al 2015, Youngblood et al 2017. We see no sign of the flare in the N v doublet, even though an increase on the order of that in the Si iii line would have been detected.…”
Section: Visit B -September 7/8 2011supporting
confidence: 67%
“…The line cores of Ca II form in the upper chromosphere/lower transition region between 5,000 and 20,000 K while the neighboring emission peaks form at cooler temperatures deeper in the atmosphere between 4,000 and 10,000 K. Since these lines yield information about the temperature structure, before stellar UV spectral observations were available, early semiempirical M dwarf chromosphere models were based on fitting ground-based Ca II K observations (Giampapa et al 1982). More recently, Youngblood et al (2017) found that the equivalent width of the Ca II K line could be used to estimate the stellar surface flux in several ultraviolet emission lines, including Lyα, and developed a scaling relationship to estimate EUV fluxes using time-averaged high resolution Ca II observations. We compare our model spectra to Keck/HIRES observations of Ca II H & K from Vogt (2011) in Figure 4.…”
Section: Visible Spectrummentioning
confidence: 99%
“…Additionally, it is important that we learn as much as we can about these planets as we prepare for atmospheric characterization with the James Webb Space Telescope (Deming et al 2009;Morley et al 2017). JWST will provide unique characterization advantages must study the UV irradiation environments of these planets, especially given that individual M stars with the same spectral type can exhibit very different UV properties (e.g., Youngblood et al 2017), and a lifetime of UV flux from the host star can have profound impacts on the composition and evolution of their planetary atmospheres.…”
Section: Introductionmentioning
confidence: 99%